AUTEKOLOGI PERTUMBUHAN PINUS (Pinus merkusii Junghuhn et de Vriese) PASKA ERUPSI DI GUNUNG GALUNGGUNG, KABUPATEN TASIKMALAYA JAWA BARAT - Asep Sadili (BERITA BIOLOGI, 2015)
Galunggung Mountain forest area in West Java of post eruption 1982 may served as a natural laboratory for studying plant development and plant growth, including pine trees. Pine trees that were planted by Perhutani at Galunggung had high prospect although they were planted at degraded areas and poor nutrient. Experimental plots were set up in two different locations at Mount Galunggung. Trunk diameter, tree height, total height, soil humidity and soil pH was measured for all pine trees inside the plot at each subplot. All measured parameters resulted in varied values with varied deviation standard. Measurement of trunk diameter, branches height and total height of pine trees in Mount Galunggung suggested that their growth rate was slow and no significant correlation among them.